A comparative study of magnetic resonance imaging and arthroscopy in internal derangement of the knee: a prospective study - Shrestha, R; Shrestha, N; Jha, R (Devdaha Medical Journal, 2026)
Introduction: Internal derangement of the knee, particularly involving the cruciate ligaments and menisci, is a common cause of pain and functional limitation. Magnetic resonance imaging (MRI) is widely used as a noninvasive diagnostic modality, whereas arthroscopy remains the gold standard for confirmation. This study aims to evaluate the diagnostic accuracy of MRI for detecting internal derangement of the knee by comparing MRI findings with arthroscopic findings. Methods: This prospective observational study included 60 patients aged 16–65 years with clinically suspected internal derangement of the knee. All patients underwent MRI using a 3 Tesla scanner, followed by diagnostic arthroscopy. MRI findings were compared with arthroscopic findings, and sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were calculated. Results: Arthroscopy identified 48 anterior cruciate ligament (ACL) tears, 11 posterior cruciate ligament (PCL) tears, 26 medial meniscal tears, and 19 lateral meniscal tears. MRI demonstrated a sensitivity, specificity, and accuracy of 87.5%, 83.3%, and 86.7% for ACL tears; 100%, 100%, and 100% for PCL tears; 84.6%, 88.2%, and 86.7% for medial meniscal tears; and 78.9%, 92.7%, and 88.3% for lateral meniscal tears. This study showed a statistically significant association between MRI and arthroscopic findings. Conclusion: MRI demonstrates high diagnostic accuracy in detecting cruciate ligament and meniscal injuries and serves as an excellent first-line investigation in patients with suspected internal derangement of the knee. Arthroscopy should be reserved primarily for therapeutic intervention.